2014
DOI: 10.21773/boun.28.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Haven Property of Gold in Turkish Financial Markets: An Investigation of the Global Financial Crisis

Abstract: This paper investigates whether gold acts as a safe haven, a hedge or a diversifier for stocks and bonds in Turkey. We employ the dynamic conditional correlation (DCC-GARCH) model which is a class of multivariate generalized autoregressive conditional heteroskedastic (GARCH) models. DCC-GARCH has two steps; the first step models the volatility dynamics in a univariate context and the second step involves computing dynamic correlations. We use daily data from June 2006 to November 2013, a period witnessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, in the same study, gold was a weak hedging asset in Turkey between 2008 and 2013. Gencer and Musoğlu (2014) show that gold acts as a hedge for stocks (BIST100 index) and bonds (10-year maturity) but is not a safe haven. Akkoç and Civcir (2019) showed that the dynamic conditional correlation of the gold price with the BIST100 is significantly high.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in the same study, gold was a weak hedging asset in Turkey between 2008 and 2013. Gencer and Musoğlu (2014) show that gold acts as a hedge for stocks (BIST100 index) and bonds (10-year maturity) but is not a safe haven. Akkoç and Civcir (2019) showed that the dynamic conditional correlation of the gold price with the BIST100 is significantly high.…”
Section: Literature Reviewmentioning
confidence: 99%